The Influence of Humidity-Control Addition on Electrospinning System for Nanofiber Formatio: Diky Anggoro, M Rizki Romadhoni, Imam Muhlas, Iim Fatimah - Diky Anggoro Diky Anggoro; M Rizki Romadhoni M Rizki Romadhoni; Imam Muhlas Imam Muhlas; Iim Fatimah Iim Fatimah (Jurnal Fisika dan Aplikasinya, 2022)
This research was conducted to determine the effect of humidity control system and collector rotational speed on electrospinning during PVA nanofiber fabrication. The humidity control system is controlled by Arduino Uno and the actuator is an air pump, and modifications are made to the air pump by adding silica gel as a more optimal humidity reducing agent. A 12 V DC-motor and L293D driver are used to control the direction and speed of rotation of the collector. The collector speed control uses the principle of Pulse Width Modulation (PWM). The humidity control system that has been made has an accuracy rate of more than 88%, and the lowest relative humidity achieved is 30%. The collector control system that has been made has an accuracy rate of more than 95%, and the lowest rotational speed is 125 RPM. Carbon nanofiber was successfully fabricated with an average diameter distribution of 43.4 nm and 79.2 nm at 30% and 40% humidity, respectively.